Type 2 Diabetes, Pre-Diabetes, and the Metabolic Syndrome The Primary Care Guide to Diagnosis and Management - Codario, Ronald A.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
Diagnosing and managing type 2 diabetes constitutes a tremendous challenge to the primary care provider confronting a rapidly growing patient population and a multiplicity of new scientific insights and therapeutic strategies. In Type 2 Diabetes, Pre-Diabetes, and the Metabolic Syndrome: The Primary Care Guide to Diagnosis and Management, Ronald A. Codario, MD-a well-known and highly respected authority on diabetes in private practice for over 30 years-details for today's busy primary care practitioners the state-of-the-art in diagnosing and managing diabetes as well as in reducing patient risk factors. Using an evidence-based approach, Dr. Codario explains, in simple clinical terms that avoid the complexity of much larger textbooks, our latest understanding of the pathophysiology of diabetes, its treatment with insulin and oral agents, and the management of its risk factors. The author also extensively reviews such major topics as the metabolic syndrome, the role of exercise and nutrition, and the key issues associated with the use of herbs and nutraceuticals. Illustrative case studies in diabetes management, an outstanding bibliography of suggested readings, and extensive chapter subheadings for quick reference make this book a practical, easy-to-read guide for physicians dealing with this killer disease. A value-added compact disk contains a companion e-book version of the book for downloading and use in the reader's PC or PDA. Also included are continuing medical education (CME) questions that provide the opportunity to acquire up to a maximum of 10 AMA/PRA category 1 CME credits. For the past 15 years, the author has given CME lectures on diabetes throughout the country. State of the art and highly practical, Type 2 Diabetes, Pre-Diabetes, and the Metabolic Syndrome: The Primary Care Guide to Diagnosis and Management offers practitioners an authoritative, well-honed approach to the successful management of their diabetic patients.
Pathophysiology of Type 2 Diabetes -- Guidelines and Classifications -- Exercise -- Nutrition -- Obesity and the Metabolic Syndrome -- Oral Agents for Type 2 Diabetes -- Insulin Use -- Macrovascular Disease -- Microvascular Disease -- Diabetic Dyslipidemia -- Hypertension in Patients With Diabetes -- Glycemic Control -- Risk Reduction in Patients With Diabetes.
Keywords: Medicine; General practice (Medicine).; Diabetes; Medicine & Public Health; Diabetes; General Practice / Family Medicine; Electronic books